Cooperative Learning With a Focus on the Social: A Pedagogical Proposal for the EFL Classroom - Janeth Juliana Contreras León; Claudia Marcela Chapetón Castro (Asociación Colombiana de Profesores de Ingles, 2016)
This article is a report of a pedagogical intervention which was developed with a group of seventh graders during their English as a foreign language class in a public school in Bogotá. It is part of an investigation in which the main purpose was to foster students' classroom interaction through the use of cooperative learning principles from a dialogical perspective that focused on social aspects of students' school lives. Thus, the instructional design incorporated a methodology that focused on the students' realities and provided opportunities for dialogue, cooperation, and reflection. From a pedagogical perspective, this experience promoted changes in the classroom practices allowing a new vision of group work, encouraging personal growth and social awareness among participants.